PENGARUH CURRENT RATIO (CR) DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM PADA PT ADI SARANA ARMADA TBK PERIODE 2014-2023 - Mutia Afriani; Simangunsong, Ria Rosalia (Management Research and Business Journal, 2025)
This research aims to determine This research aims to determine the effect of Current Ratio (CR) and Return On Asset (ROA) on the stock price of PT Adi  Sarana  Armada Tbk. The method used in this research is multiple linear regression, involving classical assumption tests, followed by partial significance testing using the t-test, while the F-test is used to assess the joint effect. The research results show that the Current Ratio (CR)  variable has a significant effect on stock prices. Meanwhile, the Return On Asset (ROA) variables do not have a significant effect on share prices. Simultaneously,  the  Current Ratio (CR) and Return On Asset (ROA) variables influence stock prices. The adjusted  R-squared  value  in  this  study  is  0,595 ,  which  means  that  the  ability  of  the independent  variable  to  explain  variations  in  the  dependent  variable  is  59,5% while  the remaining 40,5% is explained by other independent variables outside the model.